Analisis Efisiensi Pada Perusahaan Asuransi Yang Terdaftar Di Ojk Periode 2018 - 2019 Dengan Metode Dea - Hadi Aldo (Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to determine the level of efficiency in insurance companies in Indonesia. The population in this study are insurance companies registered with the OJK in the 2018-2019 period. The sampling technique was simple random sampling. The type of data used is secondary data. Data obtained by downloading the annual financial statements of each insurance company. Based on the results of the research that has been obtained, it can be concluded that of the 15 companies used as research samples, the average company has good performance efficiency. Measurements were made using the CRS and VRS models with input and output orientations.